(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
In this article, reforms in the field of legal education, stages of development, foreign and national experience in improving the quality of legal personnel are analyzed, suggestions and recommendations are given for the development of legal education.